On the Development of Cardiovascular Diseases in Children with Sleep Disorders - O. V. Kozhevnikova; L. S. Namazova-Baranova; E. A. Abashidze; V. V. Altunin; V. V. Lebedev ("Paediatrician" Publishers LLC, 2016)
Cardiovascular disease (CVD) is one of the main reasons for the high mortality rate in the world. In recent years, the importance of vascular lesions of the heart and brain in the structure of causes of death among adolescents has increased. The main risk factor for deaths and serious life-threatening complications of CVD is overweight and, in particular, obesity. Over the past 20 years the prevalence of this risk factor among children aged 6-11 years has doubled, and among teens aged 12-19 years - tripled. It is expected that the urgency of the problem will increase in the future. Over the past 40 years the association of obesity with sleep-disordered breathing has been actively studied. Therewith, obstructive sleep apnea/hypopnea syndrome is considered as one of the main causes of the development of cardiovascular accidents in adults. This review presents the results of analysis of the problem of CVD development in children with sleep disorders assessing the pediatric aspect of this problem.